Study on the association between visceral adiposity index and diabetic kidney disease in hospitalized patients with type 2 diabetes mellitus in China - Zhao, Xin; Sun, Jianbin; Xin, Sixu; Zhang, Xiaomei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to explore the correlation between visceral adiposity index (VAI) and diabetes kidney disease (DKD) in patients with type 2 diabetes mellitus (T2DM), so as to provide a clinical basis for the prevention and treatment of DKD.MethodsThis study retrospectively analyzed 1817 patients with T2DM hospitalized in the department of Endocrinology, Peking University International Hospital from January 2017 to August 2021, including 1053 males and 764 females. According the level of VAI, subjects were divided into three groups.Results(1) The results showed that with the increase of VAI level, the proportion of DKD gradually increased, and there was a statistical difference (p < 0.05). With the increase of VAI levels, there is an increasing trend in males, age, WC, BMI, WHtR, WHR, VAI, LAP, ABSI, C-Index, CUN-BAE, SBP, DBP, HbA1c, FBG, PBG, UACR, TG, while HDL-C levels show a decreasing trend (p all <0.05). (2)Logistic regression showed that after adjusting age, sex, diabetic duration, smoking, drinking, BP, blood glucose and blood lipids, high level of VAI was an independent risk factor for DKD (HR=1.38, 95% CI 1.18, 1.63). (3)The model to predict the risk of DKD using anthropometric indicators, showed that the AUC of the models ranked VAI>ABSI>C-index>WHR>AVI=BRI>BMI>CUN-BAE>LAP>WHtR.(4)The predictive ability for DKD of Model 1 with VAI was higher than that of Model 2 with BMI.ConclusionThe increase of VAI is an independent predictor of DKD occurrence in patients with T2DM, which provides a certain clinical basis for preventing the development of DKD in patients with T2DM.